Comparison of Serum Hormone Levels in Pilonidal Sinus Disease Patients by Gender - Farzaneh Nazari; Zahra Parsaiyan; Leyla Rezaei; Mahshid Mohammadpour; Kamran Mirzaei (Iranian Journal of Colorectal Research, 2022)
Background: Pilonidal sinus disease (PSD) describes an inflammation of the subcutaneous fatty tissue causing a pilonidal sinus which can lead to pus collection and tenderness. The study objective was to investigate the relationship between serum hormones, PSD and associated factors in patients referring to Khalij Fars hospital in Bushehr city, Iran in 2017. Methods: A cross-sectional study consisted of 50 patients with pilonidal sinus disease who underwent surgery in Khalij Fars hospital in Bushehr city, Iran between February and May 2017 was conducted. The patients with SPD who consented to participate in the study were enrolled in the research and subjected to review their physical signs and medical history. Hormone levels (including the serum levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH), total testosterone, dehydroepiandrosterone (DHEA), and prolactin) were measured. Results: The level of sex hormones in female patients was significantly higher in comparison with males except for testosterone (3.9±1.73 in male; 0.35±0.17 in females). The frequency of patients with normal serum levels of LH, testosterone, and prolactin was higher in females than those in the male group, whereas the rate of those with normal levels of FSH, DHEAS, and Prolactin in male patient group was higher, compared with the female group (P<0.05).Conclusion: As there are a few studies conducted on hormonal status of patients with pilonidal sinus by genders, we conducted the current study, to compare serum levels between male and female patients. Raised serum prolactin, LH, and testosterone levels in women might be contributed to increasing androgen levels and causing excessive hair growth/ hirsutism.